Entrepreneurial Infrastructure in Singapore: Developing a Model and Mapping Participation - Tan, Teck Meng (Institutional Knowledge at Singapore Management University, 2000)
Entrepreneurial infrastructure, as the term is used in this article, represents the facilities and services present within a given geographic area which encourage the birth of new ventures and the growth and development of small- and medium- sized enterprises. The model of entrepreneurial infrastructure developed here and applied to the nation of Singapore suggests that they provide support to poten tial new business owners, owners of small growing businesses, and existing small- and medium-sized enterprises by way of assisting them with tasks, physical and monetary resources, information and knowledge. This article also develops a map ping function to predict the likelihood of participation in the entrepreneurial in frastructure with the help of interviews with representatives of twelve small- and medium-sized enterprises.